Peran Love of Money, Ethical Sensitivity, Machiavellian dan Tingkat Pengetahuan dalam Mempengaruhi Persepsi Mahasiswa Mengenai Sikap Tidak Etis Akuntan - Khasanah, Syafa’atul; Fitriyah, Hadiah (Indonesian Journal Publisher, 2023)
Based on the purpose of this research, to determine the role of Love Of Money, Ethical Sensitivity, Machiavellian, Knowledge Level In Influencing Student Perceptions About Accountants' Unethical Attitudes by testing each variable. The object of this research are undergraduate students (S1) of accounting study program, Faculty of Business, Law and Social Sciences, University of Muhammadiyah Sidoarjo. The method used in the study was purposive sampling involving 150 accounting students at the Muhammadiyah University of Sidoarjo as the research sample. The analytical model used is a multiple linear regression analysis model which was carried out with the help of the SPSS version 26 for windows program. The results of this study indicate that love of money and machiavellian have a significant negative effect on students' perceptions of accountants' unethical attitudes, ethical sensitivity and level of knowledge have a significant positive effect on students' perceptions of accountants' unethical attitudes.